Dry immersion induced acute low back pain and its relationship with trunk myofascial viscoelastic changes - Plehuna, Anastasija; Green, David Andrew; Amirova, Liubov E.; Tomilovskaya, Elena S.; Rukavishnikov, Ilya V.; Kozlovskaya, Inessa B. (Frontiers in Physiology, 2022)
Microgravity induces spinal elongation and Lower Back Pain (LBP) but the pathophysiology is unknown. Changes in paraspinal muscle viscoelastic properties may play a role. Dry Immersion (DI) is a ground-based microgravity analogue that induces changes in m. erector spinae superficial myofascial tissue tone within 2 hours. This study sought to determine whether bilateral m. erector spinae tone, creep, and stiffness persist beyond 2 hours; and if such changes correlate with DI-induced spinal elongation and/or LBP. Ten healthy males lay in the DI bath at the Institute of Biomedical Problems (Moscow, Russia) for 6h. Bilateral lumbar (L1, L4) and thoracic (T11, T9) trunk myofascial tone, stiffness and creep (MyotonPRO), and subjective LBP (0-10 NRS) were recorded before DI, after 1h, 6h of DI, and 30min post. The non-standing spinal length was evaluated on the bath lifting platform using a bespoke stadiometer before and following DI. DI significantly modulated m. erector spinae viscoelastic properties at L4, L1, T11, and T9 with no effect of laterality. Bilateral tissue tone was significantly reduced after 1h and 6h DI at L4, L1, T11, and T9 to a similar extent. Stiffness was also reduced by DI at 1h but partially recovered at 6h for L4, L1, and T11. Creep was increased by DI at 1h, with partial recovery at 6h, although only T11 was significant. All properties returned to baseline 30 min following DI. Significant spinal elongation (1.17±0.20cm) with mild (at 1h) to moderate (at 6h) LBP was induced, mainly in the upper lumbar and lower thoracic regions. Spinal length increases positively correlated (Rho=0.847, p=0.024) with middle thoracic (T9) tone reduction, but with no other stiffness or creep changes. Spinal length positively correlated (Rho=0.557, p=0.039) with Max LBP; LBP failed to correlate with any m. erector spinae measured parameters. The DI-induced bilateral m. erector spinae tone, creep, and stiffness changes persist beyond 2h. Evidence of spinal elongation and LBP allows suggesting that the trunk myofascial tissue changes could play a role in LBP pathogenesis observed in real and simulated microgravity. Further study is warranted with longer duration DI, assessment of IVD geometry, and vertebral column stability.